2002
DOI: 10.1128/aac.46.6.1980-1984.2002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ciprofloxacin on Killing ofActinobacillus actinomycetemcomitansby Polymorphonuclear Leukocytes

Abstract: Actinobacillus actinomycetemcomitans, a pathogen associated with aggressive periodontitis, resists phagocytic killing by polymorphonuclear leukocytes (PMNs). It is susceptible to ciprofloxacin, which PMNs actively accumulate. This study tested the hypothesis that ciprofloxacin-loaded PMNs are more effective at killing A. actinomycetemcomitans than control PMNs. Isolated human PMNs were loaded by brief incubation with 0.5 g of ciprofloxacin/ml. Opsonized bacteria (ATCC 43718) were incubated at 37°C with control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 33 publications
2
10
0
Order By: Relevance
“…These results are consistent with those of previous studies demonstrating that A. actinomycetemcomitans cells are resistant to killing by human PMNs [14,[32][33][34]. Infection of THP-1 cells with wild-type A. actinomycetemcomitans cells resulted in a highly reproducible 2-fold increase in bacterial CFUs, and a concomitant decrease in THP-1 cell viability.…”
Section: Discussionsupporting
confidence: 82%
“…These results are consistent with those of previous studies demonstrating that A. actinomycetemcomitans cells are resistant to killing by human PMNs [14,[32][33][34]. Infection of THP-1 cells with wild-type A. actinomycetemcomitans cells resulted in a highly reproducible 2-fold increase in bacterial CFUs, and a concomitant decrease in THP-1 cell viability.…”
Section: Discussionsupporting
confidence: 82%
“…These data confirm that CIP and probably other fluoroquinolones (such as moxifloxacin, prulifloxacin, pefloxacin, and sparfloxacin) can help the host defense in the outcome of infections because they accumulate and remain active inside PMNs (20,(24)(25)(26).…”
Section: Discussionsupporting
confidence: 68%
“…In particular, CIP has a broad antibacterial spectrum, with bactericidal activity toward Gram-positive and Gram-negative aerobes (5,19); it accumulates inside the PMNs and remains active, leading to a significant reduction in the number of intracellular bacteria, such as Aggregatibacter actinomycetemcomitans (formerly Actinobacillus actinomycetemcomitans) (20).…”
Section: Discussionmentioning
confidence: 99%
“…Previous investigations of different quinolones revealed that these antibacterial agents have heterogeneous effects on the phagocytosis, the burst production, and the killing function of the respective phagocytes [4][5][6][7][8]. Because garenoxacin at therapeutic concentrations has been shown to significantly increase the CD11b expression of human PMN [5], we examined the effect of subtherapeutic to supratherapeutic concentrations of garenoxacin on phagocytosis and killing of S. aureus by human PMN.…”
mentioning
confidence: 99%
“…From 1 to 17.65 ll of appropriate quinolone dilutions were added to 100 ll heparinized whole blood immediately after blood sampling to furnish final concentrations of 0.5, 5, 100, and 1,500 mg/l, respectively. While 0.5 and 5.0 mg/l are considered to represent sub-therapeutic and normally achievable peak plasma concentrations after oral dosing of 400 mg [11], the concentration of 100 mg/l was chosen to exclude effects with higher concentrations some multiples of the maximum achievable concentrations in individual patients and for comparability with other studies [4][5][6][7][8]. In contrast, the 1,500 mg/l concentration is far outside the range of concentrations which are considered of clinical value.…”
mentioning
confidence: 99%